Activists 2004 - Holm, Hilma; Wennerhag, Magnus; Lindgren, Johan; Nordvall, Henrik; Sörbom, Adrienne (Lund University, 2014)
The purpose of the study is to give a nuanced image of activists within the Global Justice Movement in Sweden. Based on a survey carried through at three Swedish local social forums in 2004, the study highlights some aspects of the activists within this contemporary movement: political attitudes, experiences of political action, and social and demographical background variables. The questions regarding political attitudes focus on attitudes towards globalization versus the national, institutional trust, degree of identification with the movement in question, attitudes towards activism in general, etc. The questions regarding political action focuses on membership in different types of organizations, degree of activism, experience of both transnational and other forms of political activism, etc. Some of the questions are similar to those being used in international surveys made during other social forums, and in general surveys addressing questions of political attitudes, trust and behaviour.

Purpose:

To give a nuanced image of activists within the Global Justice Movement in Sweden

Undersökningens syfte är att ge en nyansrik bild av dem som är aktiva inom en samtida social rörelse, nämligen den globala rättviserörelsen i Sverige, utifrån en enkätstudie genomförd vid tre svenska sociala forum. Genom en rad frågor belyses aktivisternas politiska värderingar, tidigare erfarenhet av politiskt handlande, kön, ålder och sociala bakgrund. Frågorna om politiska värderingar avser inställning till globaliseringen och det nationella, förtroende för politiska institutioner, grad av identifikation med rörelse, syn på politiskt engagemang mm. Frågorna om politiskt handlande avser erfarenheter av konkreta politiska handlingsformer, grad av engagemang, medlemskap i organisationer eller rörelser, erfarenheter av transnationellt politiskt handlande mm. Genom samstämmighet i frågor med såväl svensk som internationell forskning om politiskt deltagande och sociala rörelser, är även ett syfte att möjliggöra komparativa studier - antingen mellan denna grupp av svenska aktivister och den svenska befolkningen, eller mellan de svenska aktivisterna och andra aktivister inom samma rörelse fast från andra länder.

Syfte:

Att ge en nyansrik bild av dem som är aktiva inom den globala rättviserörelsen i Sverige
Aktivister 2004
Keywords: participation; deltagande; international relations; internationella relationer; trust; förtroende; freedom of expression; uttrycksfrihet; membership; medlemskap; political influence; medborgarinflytande; political participation; politiskt deltagande; globalization; globalisering; social justice; social rättvisa; political institutions; politiska institutioner; social protest; social protest; demonstrations (protests); demonstrationer (protester); Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Social change; Social förändring; Social Sciences; Samhällsvetenskap; Sociology; Sociologi; Political Science; Statsvetenskap; Other Geographic Studies; Andra geografiska studier